The Correlation between Serum Concentration of Vitamin D with Vitamin D Receptor Expression and Disease Activity in Indonesian Patients with Systemic Lupus Erythematosus: Preliminary Study - Handono, Kusworini; Tanuwijaya, Laksmi Karunia; Fitri, Loeki Enggar; Kalim, Handono (Journal of Tropical Life Science, 2014)
The vitamin D role on the immune response of systemic lupus erythematosus (SLE) patient is mediated by vitamin D receptor (VDR). Low level of vitamin D correlated with disease activity in SLE patients, and circulating levels of activated vitamin D (1,25(OH)2D) contribute to VDR protein levels and its function. The objective of this study was to determine the correlation between vitamin D status with expression of VDR in peripheral blood mononuclear cell (PBMC) and the disease activity in SLE patients. The Research Subjects were 15 SLE patients (ACR 1997 criteria) from the Rheumato-Immunology Division, dr. Saiful Anwar Hospital, Malang and 5 healthy controls. Serum vitamin D (25(OH)D3) level was assessed using ELISA method. VDR expression in PBMC was assessed using immunocytochemistry technique. The disease activity was measured by Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score. This study showed no difference on VDR expression in PBMC between patient and healthy control group, but patient with vitamin D deficiency had lower VDR expression in PBMC than the other group. No difference on SLEDAI score between the group. Vitamin D status correlated positively with VDR expression in PBMC (p < 0,035, r = 0,473). However vitamin D status did not correlate with disease activity scores (p = 0,686).